2017
DOI: 10.1016/j.compositesb.2017.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Durability of bonded FRP-to-steel joints: Effects of moisture, de-icing salt solution, temperature and FRP type

Abstract: This paper investigates the effects of environmental ageing on the mechanical response of adhesively bonded double-lap shear joints made of steel and CFRP or GFRP adherents. One hundred and ninety-two specimens, 84 joints and 108 material coupons, were aged for up to three years in various environments including (i) immersion in distilled water at 20 C and 45 C, (ii) immersion in de-icing salt solution at 20 C and 45 C and (iii) exposure to 95% relative humidity at 45 C. In general, immersion at 45 C resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(68 citation statements)
references
References 42 publications
(54 reference statements)
5
53
1
9
Order By: Relevance
“…The properties of the used epoxy adhesives in dry condition are listed in Table 1, while more details on fabrication and testing can be found in [46]. Moreover, the dependency of tensile properties of the primary adhesive (STO® Lim 567) on moisture was characterized by the authors in a recent study [47], and are reported in Table 2.…”
Section: Materials and Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of the used epoxy adhesives in dry condition are listed in Table 1, while more details on fabrication and testing can be found in [46]. Moreover, the dependency of tensile properties of the primary adhesive (STO® Lim 567) on moisture was characterized by the authors in a recent study [47], and are reported in Table 2.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…The ageing temperature was chosen as 45°C to accelerate moisture diffusion. This temperature is 10°C below the adhesive glass transition temperature and is believed to safely accelerate moisture diffusion without activating unwanted reactions [49,62]. The exposure conditions were: (i) 45DW: immersion in distilled water at 45°C, (ii) 45SW: immersion in 5% NaCl salt-water at 45°C, (iii) 45RH: exposure to 95% relative humidity at 45°C.…”
Section: Environmental Conditioningmentioning
confidence: 99%
“…Zheng et al [3] investigated the durability of aluminum bonded joints under hygrothermal conditions; they suggested that exposure decreased the joint strength and changed the failure mode, and that substrate corrosion was greatly affected by elevated temperatures. Liu et al [4] and Mohsen et al [5] investigated the durability of carbon fiber-reinforced plastic joints in hygrothermal environments, and reported that the strength and failure modes were both affected by moisture and temperature. Numerous studies have reported that the interaction of temperature and moisture can accelerate joint ageing rates [6][7][8], and that strength reduction is primarily related to moisture absorption, which decreases adhesive performance and increase substrate corrosion [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Всё это приводит к тому, что возникла необходимость определять их прочностные и деформационные свойства при различных видах нагружения. В литературе этому вопросу уделено особое внимание [1][2][3][4][5]. Несмотря на многочисленные работы по анализу и интерпретации известных в литературе экспериментальных данных в настоящий момент нет полного понимания явлений, происходящих в композитах при различных видах силовых воздействий [6,7].…”
Section: Introductionunclassified
“…Среди современных композиционных материалов достаточно широкое распространение получил углепластик, представляющий собой материал из углеродных волокон, пропитанных эпоксидным связующим, который в незатвердевшем состоянии легко формуется. Это дает возможность довольно успешно использовать его для увеличения несущей способности и ремонта бетонных, железобетонных, каменных, стальных и деревянных конструкций [1][2][3][4][5]. Углепластики относятся к классу полимерных композиционных материалов из переплетённых нитей углеродного волокна, расположенных в матрице из полимерных (эпоксидных) смол.…”
Section: Introductionunclassified